Legal Protection for Child Victims of Incest Crimes: Evidence from the Aceh Women’s Empowerment and Child Protection Agency - Ishma Raihan; Yusnaidi Kamaruzzaman; Zakir, Fata; Salim, Mohammad; Susanna, Eva (Faculty of Sharia and Law, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
This study examines legal protection for child victims of incest in Aceh, with a particular focus on power relations between victims and perpetrators. In this context, incest is understood as a crime that not only violates the physical integrity of the child but also damages the victim’s psychological condition, social well-being, and sense of security, given that perpetrators generally occupy dominant positions within the family structure. Therefore, legal protection for child victims of incest requires a multidimensional approach that extends beyond law enforcement to include continuous assistance aimed at preventing revictimization. This study aims to analyze the fundamental concept of legal protection for child victims of incest and the role of the Aceh Office of Women’s Empowerment and Child Protection (DP3A) in its implementation. The research employs a qualitative method with an empirical juridical approach. The findings indicate that legal protection for child victims of incest is grounded in the principle of special protection, which recognizes children as vulnerable legal subjects due to unequal power relations. Such protection is not limited to criminal prosecution of perpetrators but also encompasses comprehensive efforts to restore the victims’ rights. Empirically, DP3A Aceh has implemented various protective measures, including psychological and physical recovery, social rehabilitation, education, and legal assistance for child victims of incest.